Accessibility and Enhancement of Cultural Heritage: Examples of Best Practices in Europe - Genovese, Rosa Anna (Protection of Cultural Heritage, 2022)
Premise. The essay will report on actions promoted at international and national level, to ensure accessibility in different sectors of social life and reduce obstacles in this field in European regulations and in the practices of Member States. The Convention adopted by UNO in 2006, stating that people with different abilities must enjoy fundamental rights and (political, economic, social, cultural) freedoms, constitutes the first great treaty of the twenty-first century concerning the change in attitude and strategies towards people bearing handicaps, to increase respect of their dignity through every possible measure. Intercultural dialogue. In light of a greater awareness on environmental issues and possible solutions, we are, therefore, all called upon to contribute to changes in the relation with our one and only Planet in order to build a new conservation ethics, which may include the values of Cultural Heritage and accept, for its protection and enhancement, the contribution of Communities, favouring intercultural dialogue. Best practices. The essay intends to stress the importance of integrated policies in promoting accessibility and the enhancement of cultural heritage, also through the examination of the best practices implemented in different European Countries. Specifically, it shall highlight how one of the criteria informing the Management Plan of the ‘Archaeological Area of Pompeii and Torre del Greco’ is based on the conservation of the archaeological heritage, with the purpose of making it accessible to the public while conserving the testimonial, formal and material features of the site, and addressing conservation issues as well as the design quality of accessibility improvements. Integrated Conservation. The quality of conservation and restoration interventions on cultural heritage will, therefore, have to be perfected through an aware fact-finding analysis, favouring the application of scientific and digital technologies, paired with a diagnostic approach capable of including the digitalisation of processes, energy efficiency, accessibility, leading to the digital management of anamnesis and control of the restoration project, based on adequate knowledge of the cultural property and its state of conservation.